Úvod do ComCom - Tomeš, Milan (Univerzita Pardubice, 2009)
This article aims to introduce to a scientific community a concept of Common company, abbreviated ComCom, which could be very interesting for solving some of today's global and personal problems. It is a vision based on division of company into two parts, combining equal ownership and individuality, which is able to move our society to a next step.
Keywords: Common Company; ComCom; equal ownership; decentralization; constitution of its citizens